EFFECT OF COMPOST MADE BASED ON TOBACCO INDUSTRY WASTE ON PLANT PRODUCTIVITY ("Conference on Universal Science Research 2023", 2025)
Experiments aimed at studying the effect of compost made on the basis of tobacco waste on the productivity of plants are studied on the example of a wheat plant.